The effects of intraperitoneal and subcutaneous insulin on function and structure of peritoneal membrane of diabetic rats - Ozalp, Goksel; Gunal, Ali Ihsan; Akpolat, Nusret; Ilhan, Nevin; Dogukan, Ayhan; Dag, Sait; Celiker, Huseyin (Oxford Univ Press, 2006)
[Abstract Not Available]
43rd Annual Congress of the European-Renal-Association/European-Dialysis-and-Transplant-Association (ERA-EDTA) -- JUL 15-18, 2006 -- Glasgow, SCOTLAND